Quiet revolution? Women’s collective empowerment and BRAC - Nazneen, Sohela; Sultan, Maheen; Chowdhury, Nobonita (Taylor & Francis, 2024)
This article was published in The Development in Practice [©2023 Rights managed by Taylor and Francis] and the definite version is available at: https://doi.org/10.1080/09614524.2023.2185182 The Article's website is at: https://www.tandfonline.com/doi/full/10.1080/09614524.2023.2185182